Avaliação histoquímica do colágeno e expressão imunoistoquímica de metaloproteinases e alfa-actina de músculo liso no sarcoide equino - Scarelli, Sarah Paschoal [UNESP] (2015)
The equine sarcoid is the most prevalent skin cancer in equine, having six clinical types described: warty, mixed, malignant, nodular, hidden, fibroblast and mixed. Evidence has shown an important influence on stromal development and progression of malignant tumors. The arrangement and quantity of collagen, the presence of myofibroblasts in the stroma or as a tumor component as well as the expression of matrix metalloproteinases (MMPs) by tumor cells, have been identified as factors that may indicate the behavior of the tumor. The objectives of this study were associate the different clinical types of equine sarcoid to expressions of MMP-1, MMP-2 and MMP-9, to the presence or absence of myofibroblasts by α-SMA expression and the characteristics and distribution of collagen, in order to determine possible markers of the biological behavior of the tumor. Typical microscopic morphological characteristics of equine sarcoid were present in the samples evaluated, but these alone can't characterize a especific clinical type. In sections stained with picrosirius red method and examined under polarized light the tumor stroma in fibroblastic and verrucous clinical types, was composed of loose and delicate collagen fibers, compatible with immature fibers in less stable lesions. Myofibroblasts were identified in equine sarcoid and the variation in distribution and intensity of alpha-SMA expression was observed even within the same clinical type. The neoplastic fibroblasts in equine sarcoid demonstrate expression MMP-1, MMP-2 and MMP-9. The verrucous and mixed types have higher MMP-2 expression than nodular clinical type, and this finding is consistent with the more aggressive potential. So there are differences between the clinical types of equine sarcoid that can be seen by the use of histochemical and immunohistochemical techniques